2023
DOI: 10.1002/smll.202302788
|View full text |Cite
|
Sign up to set email alerts
|

Designing CoHCF@FeHCF Core–Shell Structures to Enhance the Rate Performance and Cycling Stability of Sodium‐Ion Batteries

Abstract: Prussian blue analogs are well suited for sodium‐ion battery cathode materials due to their cheap cost and high theoretical specific capacity. NaxCoFe(CN)6 (CoHCF), one of the PBAs, has poor rate performance and cycling stability, while NaxFeFe(CN)6 (FeHCF) has better rate and cycling performance. The CoHCF@FeHCF core–shell structure is designed with CoHCF as the core material and FeHCF as the shell material to enhance the electrochemical properties. The successfully prepared core–shell structure leads to a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…The methodology proposed in this work can tackle the challenge of eliminating interstitial water and uplifting the average potential by tuning the low-spin redox of PBA. CoFeHCF outperforms various SIB cathodes reported earlier such as CoHCF@FeHCF (118 mAh g –1 @ 17 mA g –1 ), Na x Zn y Fe 1– y [Fe(CN) 6 ] (132 mAh g –1 @ 15 mA g –1 ), Na 1.73 Fe[Fe(CN) 6 ]·3.8H 2 O(116 mAh g –1 @ 10 mA g –1 ), Na 1.58 Fe[Fe(CN) 6 ] 0.87 ·2.38H 2 O (123 mAh g –1 @ 15 mA g –1 ), Na 1.59 Ni 0.65 Fe 0.35 [Fe(CN) 6 ] 0.97 ·2.28H 2 O (128 mAh g –1 @ 10 mA g –1 ), etc . (A detailed comparison of various reports is shown in Table S2.)…”
Section: Resultsmentioning
confidence: 79%
See 3 more Smart Citations
“…The methodology proposed in this work can tackle the challenge of eliminating interstitial water and uplifting the average potential by tuning the low-spin redox of PBA. CoFeHCF outperforms various SIB cathodes reported earlier such as CoHCF@FeHCF (118 mAh g –1 @ 17 mA g –1 ), Na x Zn y Fe 1– y [Fe(CN) 6 ] (132 mAh g –1 @ 15 mA g –1 ), Na 1.73 Fe[Fe(CN) 6 ]·3.8H 2 O(116 mAh g –1 @ 10 mA g –1 ), Na 1.58 Fe[Fe(CN) 6 ] 0.87 ·2.38H 2 O (123 mAh g –1 @ 15 mA g –1 ), Na 1.59 Ni 0.65 Fe 0.35 [Fe(CN) 6 ] 0.97 ·2.28H 2 O (128 mAh g –1 @ 10 mA g –1 ), etc . (A detailed comparison of various reports is shown in Table S2.)…”
Section: Resultsmentioning
confidence: 79%
“…In this regard, Kong et al designed a core–shell structure of cobalt hexacyanoferrate (CoHCF) and FeHCF, significantly enhancing composited PBA cathode’s rate performance and cycling stability. The CoHCF is used as a core that offers two-electron redox reactions with high reversible capacity but lacks capacity retention at high current rates; hence, FeHCF is used as a shell in the composite, which provides excellent stability at high current rates and facilitates high electrical conductivity for easy transfers of electrons . Similar studies of composite formation and structural modifications are reported, such as HCS-PBMN and CoNi-HCF@Ni-HCF which indicates the electrochemical properties of PBA can be tuned by adopting element substitution and structural modifications.…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…The Prussian blue analogues (PBAs) A j M k [M(CN) 6 ] l • n H 2 O, where M' and M are 3d transition metal ions and A is an interstitial cation, attract great attention due to their rich palette of properties such as room-temperature ferromagnetism [1,2], photomagnetism [3, [4], magnetic sensitivity to external pressure [5,6], and the negative thermal expansion [7]. Thin films of PBAs are therefore considered as interesting materials for power supply and storage [8][9][10][11], ion-sieving membranes [12], or future molecule-based spintronic devices [13,14]. One of the most important advantages of PBAs is their highly symmetrical structure.…”
Section: Introductionmentioning
confidence: 99%